2020
DOI: 10.3390/nano10071360
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Hydrogenation over Unsupported Fe-Co Nanoalloy Catalysts

Abstract: The thermo-catalytic synthesis of hydrocarbons from CO2 and H2 is of great interest for the conversion of CO2 into valuable chemicals and fuels. In this work, we aim to contribute to the fundamental understanding of the effect of alloying on the reaction yield and selectivity to a specific product. For this purpose, Fe-Co alloy nanoparticles (nanoalloys) with 30, 50 and 76 wt% Co content are synthesized via the Inert Gas Condensation method. The nanoalloys show a uniform composition and a size distribution bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Zn(Pb) electrodes were prepared by a one‐step co‐electrodeposition strategy by which a series of Zn(Pb) films with controllable lead concentrations can be produced (Table S1 , Supporting Information). X‐ray diffraction (XRD) measurements confirmed the Zn(Pb) structure to include metallic Zn, although the (002), (100), and (101) peaks are shifted toward higher angles and split with increasing Pb content, [ 31 ] as shown in Figure 1 a . This trend refers to the compression and tension [ 32 ] of Zn phases due to the embedded Pb atoms supported by the XRD simulation presenting a similar pattern, as shown in Figure S1 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Zn(Pb) electrodes were prepared by a one‐step co‐electrodeposition strategy by which a series of Zn(Pb) films with controllable lead concentrations can be produced (Table S1 , Supporting Information). X‐ray diffraction (XRD) measurements confirmed the Zn(Pb) structure to include metallic Zn, although the (002), (100), and (101) peaks are shifted toward higher angles and split with increasing Pb content, [ 31 ] as shown in Figure 1 a . This trend refers to the compression and tension [ 32 ] of Zn phases due to the embedded Pb atoms supported by the XRD simulation presenting a similar pattern, as shown in Figure S1 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Calizzi et al. reported that, on unary Fe and Co nanoparticles, the major products were CO and CH 4 , respectively . However, on FeCo nanoalloys with different metal ratios, they observed the formation of C 2 to C 5 hydrocarbons and suggested that the synthesis proceeds by RWGS–FT reactions.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is related to their partial oxidation during thermal treatment. Finally, it is worth adding that the obtained results can be considered as an important source of information for the application of thermally-treated Fe-Co nanochains as magnetic and microwave absorbers [ 27 , 28 ] or in catalysis [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results are collected and comprehensively described in this work. Moreover, it is worth noting that they can be considered as an important source of information for the application of the thermally-treated iron-cobalt Wire-like nanochains in the magnetic and microwave absorbers [ 27 , 28 ] or catalysis [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%